Effect of ammonium nitrogen on microalgal growth, biochemical composition and photosynthetic performance in mixotrophic cultivation. (February 2019) - Li, Xiaoting; Li, Wei; Zhai, Jun; Wei, Haoxuan; Wang, Quanfeng
Highlights: Mixotrophic microalga showed better growth and stronger tolerance to high ammonium. The synthesis of microalgal carbohydrates was inhibited by higher ammonium. Ammonium increased microalgal lipids in mixotrophic cultivation. Inhibition to the photosynthetic activity was intensified by elevated ammonium. Abstract: To enhance microalgal growth and optimize ammonium utilization, the effect of ammonium on microalgal growth, biochemical composition and photosynthetic performance were investigated by mixotrophic cultivation of microalga Spirulina platensis comparing with autotrophic cultivation. The results indicated that elevated ammonium significantly affected the microalgal growth, but the microalga in mixotrophic cultivation showed better growth and stronger tolerance to higher ammonium. The microalgal proteins were increased by increasing nitrogen concentration. The synthesis of microalgal carbohydrates was inhibited by higher ammonium, especially in mixotrophic cultivation. The addition of ammonium decreased the microalgal lipids in autotrophic cultivation but increased microalgal lipids in mixotrophic cultivation. Ammonium negatively affected the microalgal photosynthetic performance. The inhibition was intensified by elevated ammonium, inducing stronger photosystem protection mechanism, particularly in mixotrophic cultivation. The rate of ammonium inhibition to the microalgal photosystem was quick in the early stage by decreasing electron transport rate of PS II.